2016
DOI: 10.1016/j.bbr.2016.01.038
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral and monoamine perturbations in adult male mice with chronic inflammation induced by repeated peripheral lipopolysaccharide administration

Abstract: Considering the limited information on the ability of chronic peripheral inflammation to induce behavioral alterations, including on their persistence after inflammatory stimuli termination and on associated neurochemical perturbations, this study assessed the effects of chronic (0.25 mg/kg; i.p.; twice weekly) lipopolysaccharide (LPS) treatment on selected behavioral, neurochemical and molecular measures at different time points in adult male C57BL/6 mice. Behaviorally, LPS-treated mice were hypoactive after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 92 publications
(110 reference statements)
1
11
0
Order By: Relevance
“…The cerebral DA levels showed a decreasing trend although the mRNA levels of th (DA synthesizing enzyme) and dard1a (DA receptor) genes were not altered from adolescence to adulthood. Aberrant cerebral striatal and prefrontocortical DA and 5-HT expression associated with anxiety and hypoactivity for the mice repeatedly exposed to LPS [ 56 ]. Thus, 5-HT or DA deficiency in the brain might be an important causative factor of anxiety- and ASD-like behaviors in humans or animal models [ 6 , 9 , 57 , 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…The cerebral DA levels showed a decreasing trend although the mRNA levels of th (DA synthesizing enzyme) and dard1a (DA receptor) genes were not altered from adolescence to adulthood. Aberrant cerebral striatal and prefrontocortical DA and 5-HT expression associated with anxiety and hypoactivity for the mice repeatedly exposed to LPS [ 56 ]. Thus, 5-HT or DA deficiency in the brain might be an important causative factor of anxiety- and ASD-like behaviors in humans or animal models [ 6 , 9 , 57 , 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…Usually, adult animals more frequently developed protracted anxiety or depressive symptoms when compared to controls. Additionally, some studies injected repeated LPS doses [163][164][165][166][167][168][169][170][171][172][173][174].…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have demonstrated that systemic LPS stimulation can cause a loss of DAergic neurons and other PD-related pathological abnormalities (Biesmans et al, 2013;Krishna, Dodd, & Filipov, 2016). A single intraperitoneal injection of LPS at 5 mg/kg leads to significant DAergic neuron damage in C57BL/6 mice 7 months after LPS treatment (Qin et al, 2007).…”
Section: Discussionmentioning
confidence: 99%